Feasibility of introducing integrated disease surveillance and response into curricula of public health training institutions in Sierra Leone: the process and lessons learnt - Njuguna, Charles; Mbawa, Abdul; Njeru, Ian; Nuwagira, Innocent Bright; Vandi, Mohamed; Kanu, Joseph Sam; Squire, James Sylvester; Koroma, Aminata Tigiedankay; Renner, Ade; Musoke, Robert; Gachari, Wilson; Caulker, Victor; et al. (Frontiers in Public Health, 2024)
IntroductionResponse to public health emergencies is a big challenge in African countries due to inadequate workforce. Integrated Disease Surveillance and Response (IDSR) is a strategy implemented by African member states of WHO to strengthen capacity for disease surveillance and response at all levels. Despite successful implementation of IDSR in most countries, one of the challenges that persists is that of inadequate trained workforce competent enough for public health surveillance. Introducing IDSR pre-service curriculum in public health training institutions has therefore been recommended by WHO as one of the strategies to sustainably address the human resource challenge. We report on the process and lessons learnt in Sierra Leone which was the first country to implement the recommendation.MethodsThis was a descriptive study where the process of introducing and implementing IDSR pre-service curriculum in Sierra Leone was documented from 2018 to 2024. Data was collected through observation, documentation and analysis of key processes that took place. These processes included, inter alia, advocacy with public health training institutions, development of the IDSR pre-service curriculum and incorporation of the curriculum into the existing training programs of colleges and universities.ResultsIDSR preservice curriculum was developed and successfully introduced in eight targeted public health training institutions in Sierra Leone from September 2021. Training content was adapted from the 3rd Edition of IDSR technical guidelines developed by WHO in 2019. As at February 2024, more than 4,200 students had started taking IDSR modules in the eight institutions with 2,108 having completed and graduated. During the process, we learned that key enablers to success were government support, good advocacy with the training institutions and training of lecturers on IDSR. Main challenges were the long process of curriculum approval by training institutions and handling of big classes of students without adequate training materials.ConclusionIntroducing IDSR into the preservice curricula of public health training institutions is feasible and can provide a reliable and continuous supply of a trained workforce ready to be utilized for IDSR in Africa. Successful implementation requires advocacy with training institutions as well as regular monitoring of the implementation to maintain good quality.